Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M131 - Peter Brandt; Marek Ostrowski (PANGAEA, 2023)
Raw multibeam bathymetry data were recorded on RV METEOR during M131 using Kongsberg EM 122 multibeam echosounder. The cruise took place between 7.10.2016 - 12.11.2016, (Recife, Brasil - Walvis Bay, Angola) in the Atlantic Ocean. Data were recorded in the Angola EEZ and throughout the whole time spend outside EEZs with an approximate average depth of around 2000m. To enhance MBES data accuracy, real-time measurement by SV-Profiler at transducer depth were directly applied during acquisition with SIS Seafloor Information System. Data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors can be expected due to the lack of proper SVP. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. Ancillary sound velocity profiles (SVP) from the cruise are also archived at BSH, and these files have been added to the dataset. During M131, data acquisition and provision were accomplished to support hydrographic and current measurements along 11°S across the Atlantic, hydrographic and current cross-shelf sections in the Benguela upwelling system, microstructure measurements, mooring service, glider deployments and recoveries and sediment samples. Data publication is done through work package 2 of the EU Horizon 2020 project iAtlantic- Integrated Assessment of Atlantic Marine Ecosystem in Space and Time (https://www.iatlantic.eu/).